Public Service Integrity Perception: Case Study In Kutai Kartanegara Regency, Indonesia - MUTIARIN, DYAH (Universitas Muhammadiyah Yogyakarta, 2014)
This paper was aimed to measure the integrityof public service at Kutai KartanegaraRegency, East Borneo Province, Indonesia.The public service integrity can be seen frommany perspective such as how the citizenssatisfied with the public services provided bythe government, how the public perception oncombating corruption, and how success thegovernment providing minimum servicestandard to the public at large. This threeforms of public service integrity was the mainfocuses of this research in Kutai Kartanegararegency. The phenomenon of public service inKutai Kartanegara Regency shown out of thetracks and missing to convey the importanceof public service values, characterized byuncertainty of charges, time, and procedures.The research used the quantitative methodsby scoring 3 indexes, which are the CitizenSatisfaction Index, Corruption PerceptionIndex, and Minimum Service Standard Index.This research used Non- probability Samplingmethod, also Judgment Sampling procedure,in the development and compilation of thecitizens satisfaction index. There were 57local government agencies that served as thesamples. The results of this research were thepublic service integrity perceptions in KutaiKartanegara regency was need to beimproved on the quantity and quality of publicservice delivery, commitment and efforts tocreate a clean government, transparency andaccountability espe cially on e-procurementand to implement minimum